ONIOM and ab-initio calculations on the mechanism of uncatalyzed peptide bond formation - Monajemi, H.; Daud, Mohammad Noh; Zain, Sharifuddin Md; Wan Abdullah, Wan Ahmad Tajuddin (NRC Research Press, 2012)
Finding a proper transition structure for the peptide bond formation process can lead one to a better understanding of the role of ribosome in catalyzing this reaction. Using computer simulations, we performed the potential energy surface scan on the ester bond dissociation of P-site aminoacyl-tRNA and the peptide bond formation of P-site and A-site amino acids. The full fragments of initiator tRNA(i)(met) and elongator tRNA(phe) are attached to both cognate and non-cognate amino acids as the P-site substrate. The A-site amino acid for all four calculations is methionine. We used ONIOM calculations to reduce the computational cost. Our study illustrates the reduced rate of peptide bond formation for misacylated tRNA(i)(met) in the absence of ribosomal bases. The misacylated elongator tRNA(phe), however, did not show any difference in its PES compared with that for the phe-tRNA(phe). This demonstrates the structural specification of initiator tRNA(i)(met) for the amino acids side chain.